2022
DOI: 10.3390/cells11020310
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in Solid Tumors

Abstract: Myeloid-derived suppressor cells (MDSCs) are one of the main suppressive cell population of the immune system. They play a pivotal role in the establishment of the tumor microenvironment (TME). In the context of cancers or other pathological conditions, MDSCs can differentiate, expand, and migrate in large quantities during circulation, inhibiting the cytotoxic functions of T cells and NK cells. This process is regulated by ROS, iNOS/NO, arginase-1, and multiple soluble cytokines. The definition of MDSCs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 195 publications
(202 reference statements)
0
36
0
1
Order By: Relevance
“…The majority (90%) of NK cells in PBMCs, which show less response to cytokine stimulation, are mature cells. Mature NK cells have several direct cytolytic mechanisms against tumors and pathogen-infected cells, which include (i) lysis by cytolytic granules such as granzyme and perforin, (ii) death receptor (DR) mediated apoptotic processes such as TNF-related-apoptosis-inducing-ligand (TRAIL)/TRAIL receptors or induction of apoptosis by FasL/Fas ligation, and (iii) antibody dependent cell-mediated cytotoxicity (ADCC) ( 377 , 378 ). In tumor models, the cytotoxic activity of NK cells has been shown to be inhibited by the cell–cell interaction with MDSCs (pathogenically activated neutrophils), reducing NK cell activation by IL-2 and perforin production and a significant decline in the ability of NK cells to attack tumor cells ( 379 ).…”
Section: Interaction Of Natural Killer (Nk) Cells and Neutrophilsmentioning
confidence: 99%
“…The majority (90%) of NK cells in PBMCs, which show less response to cytokine stimulation, are mature cells. Mature NK cells have several direct cytolytic mechanisms against tumors and pathogen-infected cells, which include (i) lysis by cytolytic granules such as granzyme and perforin, (ii) death receptor (DR) mediated apoptotic processes such as TNF-related-apoptosis-inducing-ligand (TRAIL)/TRAIL receptors or induction of apoptosis by FasL/Fas ligation, and (iii) antibody dependent cell-mediated cytotoxicity (ADCC) ( 377 , 378 ). In tumor models, the cytotoxic activity of NK cells has been shown to be inhibited by the cell–cell interaction with MDSCs (pathogenically activated neutrophils), reducing NK cell activation by IL-2 and perforin production and a significant decline in the ability of NK cells to attack tumor cells ( 379 ).…”
Section: Interaction Of Natural Killer (Nk) Cells and Neutrophilsmentioning
confidence: 99%
“…Greater understanding of the mechanism which predispose to We found that mHLA-DRd is a distinct immunological parameter, demonstrating stability over a twelve month period, that does not correlate with clinically utilised inflammatory markers, major circulating cytokines, or circulating lymphocytes, but appears to reflect accumulation of CD14 + CD11b + CD33 + HLA-DR lo cells within the monocyte compartment. Monocytic myeloidderived suppressor cells (mMDSC) are a heterogenous population and a definitive marker is yet to be described (31,33), but cells with this phenotype have been previously demonstrated to suppress T and NK cell proliferation in vitro through a number of mechanisms, including induction of regulatory T cells, metabolite depletion, and secretion of reactive oxygen species (ROS) and nitric oxide (NO) (34,35). Recent work in mice comparing MSDC populations and transcriptional pathways in the setting of chronic viral infection or malignancy suggests different mechanisms may predominate depending on the context of the stimulus (36).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly increased immature myeloid cells have been observed in the bone marrow and peripheral blood of patients with cancer ( Cheng et al, 2021 ), and the presence of enriched MDSCs have been related to poor prognosis for multiple types of cancer ( Jiang et al, 2015 ; Tian et al, 2015 ; De Cicco et al, 2020 ). In fact, throughout the entire pathological process that leads to tumor formation, MDSCs increase up to10-fold and migrate to the periphery, exerting their suppressor activity interfering with the normal functions of circulating T and other immune cells involved in the anti-tumor immunity ( Safarzadeh et al, 2019 ; Nakamura and Smyth, 2020 ; Ma et al, 2022 ). Unlike mice’s MDSCs, where these cells have been well characterized, human MDSCs are less clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike mice’s MDSCs, where these cells have been well characterized, human MDSCs are less clearly defined. Typically, they are described as lineage cells that co-express high levels of CD33 and CD11b surface markers but lack HLA-DR. Human CD33 + CD11b + HLA-DR − MDSCs can also be subdivided in three distinct populations of CD14 + CD15 − monocytic-MDSCs (M-MDSCs), CD15 + CD66b + CD14 − granulocytic-MDSCs (G-MDSCs) and CD14 − CD15 − early-MDSCs (E-MDSCs), which comprised more immature progenitors ( Gabrilovich and Nagaraj, 2009 ; Mandruzzato et al, 2016 ; Ma et al, 2022 ) myeloid markers, such as PD-L1, CD40, CD49d, CD80, CD115, and CD124, which all mediate immunosuppression, has also been discovered to describe specific patterns of MDSCs ( Gabrilovich and Nagaraj, 2009 ; Mandruzzato et al, 2016 ; Ma et al, 2022 ). Two functional proteins, such as CCAAT/enhancer-binding protein (c/EBPβ) and STAT3, which promote generation, differentiation, and expansion of MDSCs, despite are not surface markers, could help to define two different MDSCs subgroups (CD11b + HLA-DR − c/EBPβ + and CD33 + HLA-DR - STAT3 + ) and could provide new diagnostic and therapeutic tools for cancer immunotherapy ( Lechner et al, 2011 ; Wu et al, 2011 ; Wang et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation